2021
DOI: 10.3390/ani11092569
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Control of Paratuberculosis in Dairy Calves by Only Changing the Quality of Milk Fed to Calves

Abstract: One of the important routes of Mycobacterium avium subsp. paratuberculosis (MAP) transmission in dairy calves is milk. The aim of the present study was to assess the efficacy of milk treatments to prevent MAP infection transmission to calves. A one-year longitudinal study was carried out. Newborn calves were assigned to one of four experimental groups: 5 calves received naturally MAP-contaminated milk, 5 calves received copper treated milk, 4 calves were fed calf milk replacer, and 3 were fed UHT pasteurized m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It seems that MAP also has the ability to mount an adaptive response to a copper stressor, which would explain the observed tolerance to these stressors in some MAP cells [38,39]. Regarding the effect of copper on MAP, Tejeda et al [39] found that the cell wall of MAP did not suffer any type of alteration once treated with copper ions.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that MAP also has the ability to mount an adaptive response to a copper stressor, which would explain the observed tolerance to these stressors in some MAP cells [38,39]. Regarding the effect of copper on MAP, Tejeda et al [39] found that the cell wall of MAP did not suffer any type of alteration once treated with copper ions.…”
Section: Discussionmentioning
confidence: 99%
“…The reported efficacy of copper ions in the control of MAP amounts to an interesting scientific finding and suggests a potential tool for the control of this important potential zoonotic pathogen [21]. The idea is to recommend the application of this decontaminating principle to block an important infection transmission route from the most infectious animals (cows) to the most susceptible animals (calves) via milk consumption [24].…”
Section: Discussionmentioning
confidence: 99%
“…As JD is incurable, early detection and isolation of infected animals prior to shedding is critical to reduce disease incidence. Fecal PCR and serum ELISA have been widely used to detect infected cattle, but their sensitivity is low, as shedding occurs intermittently, and serum antibody titers against MAP only increase in late stages of infection [ 3 , 4 , 15 , 16 , 17 ]. Economic losses, animal welfare concerns, and potential zoonotic risks associated with JD have driven research to improve early diagnosis and new diagnostic techniques [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%